OVERPRESSURE, COMPARTMENTALIZATION, AND PROPERTY OF RESERVOIRS IN OIL AND GAS FIELD, BLOCK AA, NORTHERN MADURA PLATFORM, EAST JAVA BASIN - Suryana, Ecep
The research is conducted in the Northern Madura Platform, East Java Basin, which is Eocene to Miocene in age and is proven as a hydrocarbon producer in the Kujung and Ngimbang Formations. Tectonically, this basin is located in active tectonic regions that may allow overpressure to occur.